DESAIN PLTS OFF-GRID BERDASARKAN ANALISIS OTONOMI BATERAI LEAD ACID OPZV DI ADIDAYA WORKSHOP, JAKARTA BARAT - Jonathan Oliver Ken; I Nyoman Setiawan; I Wayan Sukerayasa (Jurnal SPEKTRUM, 2023)
The design of Off-Grid PV at Adidaya Workshop as an additional electrical energy supplier is based on the load requirements used for equipment and operations at the workshop. In addition to requests from the company itself, the design of Off-Grid PV is carried out to supply electrical energy to essential loads and other educational purposes. The Off-Grid PV design was carried out with the first step of field observations at Adidaya Workshop, measuring the roof area, daily electricity load profile with a Power Quality Analyzer measuring instrument, and calculating the capacity requirements of the Off-Grid PV system according to the Adidaya Workshop load. The Off-Grid PV design was carried out with 4 scenarios based on variations in solar panels and batteries. Researchers calculated the capacity of the PV system and used PVSyst software as a design simulation so that a report was obtained based on field data. In the simulation results with PVSyst, the best performance ratio is obtained which is worth 68.3% obtained from scenario 3 with a variation of 600 Wp solar panels and 540 Ah batteries and the largest yield energy output is obtained from scenario 4.